COMMUNICATIVE FOREIGN LANGUAGE TEACHING: SUGGESTED CLASSROOM PROCEDURE FOR TEACHING SPEAKING - ZULHERMINDRA ZULHERMINDRA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
Teaching speaking to students at any level seems to be a big problem to English teachers. As a result, this skill seems to be ignored. Though, some of the teachers have tried hard to teach this skill, the result does not reflect the competency that the students are supposed to master. This is due to the inappropriate techniques and classroom procedures applied in the classroom. Consequently, the learning processes tend to be boring. This paper is intended to introduce some suggested techniques and a sample classroom procedure in terms of communicative language teaching. Kata kunci: CLT, speaking, classroom procedure, teaching, technique